ANALISIS AKTIVITAS BELAJAR SISWA DALAM PEMBELAJARAN IPS DENGAN MENGGUNAKAN MODEL PEMBELAJARAN DIFERENSIASI KELAS V SD NEGERI 63 OKU - Anggraini, Dina; Murjainah, Murjainah; Heryanto, A (EduStream: Jurnal Pendidikan Dasar, 2024)
Differentiated learning is an effort to modify the learning process in the classroom to accommodate the learning needs of each student, with modifications relating to learning readiness, learning profiles, and interests. Learning activities are closely related to students' interest in a subject. The aim of this research is to determine students' learning activities in Social Studies learning in Elementary School using the differentiated learning model. The research object is fifth-grade students at elementary school. The method used in this research is qualitative method, employing data collection techniques such as observation, interviews, and documentation. The results show that students' learning activities are good, where students are active during the learning process, able to complete tasks assigned by the teacher, and have applied the differentiated learning model according to the learning strategies implemented in elementary school based on students' learning needs consisting of three aspects: readiness to learn, interest in learning, and learning profiles. There are challenges during the learning process where some students pay less attention when the teacher explains the material.